Konstruksi Teologi Kearifan Lokal Melalui Kajian Identitas Sosial, Kebutuhan Mendasar dan Orientasi Nilai Budaya Masyarakat Desa Teremaal di Kabupaten Minahasa Utara - Marde Christian Stenly Mawikere; Sudiria Hura (Peneliti.net, 2022)
The research in this article examines the Dynamics of Social Identity, Felt Needs and Orientation of Cultural Values ​​of the Local Community of Teremaal Village as a social group in North Minahasa Regency, North Sulawesi Province. This study shows that the villagers historically come from a community background that has rich cultural and natural resources, potential and local wisdom, which then by interaction and influence from outside communities have an open attitude to social change and community development. Thus, this study will contribute and stimulate a critical, creative and dynamic dialogue for the efforts of a complete development approach, both physically, emotionally and spiritually as well as contextually for the local community of Teremaal village. This is one of the elements in constructing a contextual theology, namely the theology of local wisdom (or theology from below) which leads to a holistic ministry